Phenotypic Analysis of Urothelial Exfoliated Cells in Bladder Cancer via Microfluidic Immunoassays: Sialyl-Tn as a Novel Biomarker in Liquid Biopsies - Carvalho, Sandra; Abreu, Catarina M.; Ferreira, Dylan; Lima, Luís; Ferreira, José A.; Santos, Lúcio L.; Ribeiro, Ricardo; Grenha, Vânia; Martínez-Fernández, Mónica; Duenas, Marta; Suárez-Cabrera, Cristian; Paramio, Jesus M.; et al. (Frontiers in Oncology, 2020)
Bladder cancer is the most common malignancy of the urinary tract, having one of the highest recurrence rates and progression from non-muscle to muscle invasive bladder cancer that commonly leads to metastasis. Cystoscopy and urine cytology are the standard procedures for its detection but have limited clinical sensitivity and specificity. Herein, a microfluidic device, the UriChip, was developed for the enrichment of urothelial exfoliated cells from fresh and frozen urine, based on deformability and size, and the cancer-associated glycan Sialyl-Tn explored as a putative bladder cancer urinary biomarker. Spiking experiments with bladder cancer cell lines showed an isolation efficiency of 53%, while clinical sample analyses revealed retention of cells with various morphologies and sizes. In situ immunoassays demonstrated significantly higher number of Sialyl-Tn-positive cells in fresh and frozen voided urine from bladder cancer patients, compared to healthy individuals. Of note, urothelial exfoliated cells from cryopreserved urine sediments were also successfully isolated by the UriChip, and found to express significantly high levels of Sialyl-Tn. Remarkably, Sialyl-Tn expression is correlated with tumor stage and grade. Overall, our findings demonstrate the potential of UriChip and Sialyl-Tn to detect urothelial bladder cancer cells in follow-up and long-term retrospective studies.